Acute papillary muscle infarction and rupture in the puerperium complicating Libman–Sacks endocarditis in a patient with systemic lupus erythematosus and antiphospholipid syndrome: a case report. Issue 4 (13th November 2019) - Curtis, Elizabeth; Corkill, Michael; Amir, Nezar; Haydock, David
Abstract: Background: Acute heart failure caused by severe mitral regurgitation (MR) due to papillary muscle rupture has been described in the puerperium by case reports; however, the majority of cases of papillary muscle rupture are caused by myocardial infarction. We describe papillary muscle rupture occurring in the postpartum period in a patient with systemic lupus erythematosus (SLE), antiphospholipid syndrome (APLS), and chronic Libman–Sacks endocarditis and explore the multifactorial nature of the papillary muscle infarction and rupture in the setting of postpartum fluid shifts, chronic myocardial injury from Libman–Sacks, and high thrombotic risk. Case summary: A 29-year-old woman presented with acute heart failure 2 weeks' postpartum and was found to have acute MR due to a flail leaflet caused by papillary muscle rupture. She proceeded to emergency surgery with mitral valve (MV) replacement and the histology revealed evidence of chronic Libman–Sacks endocarditis and papillary muscle infarction with thrombi in the intramyocardial arteries. Discussion: This is the second case report of papillary muscle rupture in the puerperium in a patient with SLE in the literature, the other case was caused by catastrophic APLS. However, in this case, the cause of the rupture is likely to be multifactorial; as a consequence of thrombosis in the microvasculature causing isolated papillary muscle ischaemia, and fibrosis of the muscle due to chronic Libman–Sacks endocarditis resulting in limited pliability which caused rupture of the papillary muscle when faced with the added stress of increased volume that occurs in the puerperium.